EFFECT OF SAUROPUS ANDROGYNUS LEAVES EXTRACT (SALE) ON FAT DEPOSITION IN BROILER FED LOW PROTEIN DIETS - Santoso, U.; Kususiyah, K.; Fenita, Y. (Journal of the Indonesian Tropical Animal Agriculture, 2013)
The present study was designed to evaluate the effect of Sauropus Androgynus Leaves Extract(SALE) on broiler chickens fed low protein diets. Eighty four mixed broiler chickens (male:female =1:1) aged 20 days were distributed to seven treatment groups as follows: 1) Broilers fed 19% proteinwithout SALE (P0); 2) Broilers fed 19% protein plus 4.5 g SALE/kg (P1); 3) Broilers fed 17% proteinplus 4,5 g SALE/kg (P2); 4) Broilers fed 15% protein plus 4.5 g SALE/kg (P3); 5) Broilers fed 19%protein plus 9 g SALE/kg (P4); 6) Broilers fed 17% protein plus 9 g SALE/kg (P5); 7) Broilers fed15% protein plus 9 g SALE/kg (P6). Experimental results showed that supplementation of Sauropusandrogynus extract to low protein diets had no effect on meat colour, haemorrhages scale in breastmeat, and fatty liver score (P>0.05), but it significantly affected haemorrhages scale in thigh meat(P<0,01), shank colour, meat taste and flavour (P<0.05). In addition, supplementation of the extractsignificantly affected meat fat content (P<0.05) and meat cholesterol content (P<0.01), but it had noeffect on meat protein content (P>0.05). It can be concluded that the leaves extract of Sauropusandrogynus supplementation at level of 9 g/kg diets normalized fat deposition in broiler chickens fedlow protein diets. SALE improved broiler meat qualities.